Pengaruh Orientasi Terhadap Tingkat Kecemasan Pasien Yang Perawat Di Ruang Interna RSUD Pare Kabupaten Kediri - Helena Lenawati, - (2005)
Hospitalized patients often experience anxiety, grading from mild tosevere. Due to this cause, nurses cannot perform orientation optimally. Patientsoften say that they do not know where they can obtain nursing care or whatprocedures that will be taken. In contrast, patients receiving adequate explanationdemonstrate positive response. The objective of this study was to identify theeffect of orientation on the level of anxiety.This study used one group pretest posttest pre-experimental design, withpopulation comprising all patients in Internal Wards, Regional Hospital, Pare,Kediri. Sample consisted of 56 individuals, taken using purposive sampling. Theindependent variable was the orientation to the patients, and the dependentvariable was level of anxiety. Data were collected using questionnaire. Data wereanalyzed using Wilcoxon's Signed Ranks test with significance level ofp:::. 0.05.Results revealed that orientation had effect on the patients' level of anxiety(p = 0.001 z = -3.289). Respondents with moderate level of anxiety prior toorientation had no anxiety at all after orientation. The orientation, carried outaccording to the author's pre-established procedure, showed significant effect onthe reduction of the patient's level of anxiety. Orientation standard for newlyadmittedpatients should be established by all nurses.